1950
DOI: 10.1021/ac60037a024
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Volumetric Analysis

Abstract: VOLUME 2 2, NO. 1, JANUARY 1950 97 o-and p-cresols have been determined gravimetrically by the cresoxyacetic acid method (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
1961
1961

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…That the precipitation was complete was shown by measurement of the optical density at 260 m~ after removal of the uranyl salt by dialysis. After removal of the precipitate the quantity of uranyl ion remaining in solution was determined by complexing with ferrocyanide (31). The amount of complex formed was determined by measuring the optical density of the solution at 500 m# on either a Beckman DU or Cary Model 11 recording spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That the precipitation was complete was shown by measurement of the optical density at 260 m~ after removal of the uranyl salt by dialysis. After removal of the precipitate the quantity of uranyl ion remaining in solution was determined by complexing with ferrocyanide (31). The amount of complex formed was determined by measuring the optical density of the solution at 500 m# on either a Beckman DU or Cary Model 11 recording spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens prepared for observation in the electron microscope showed primarily long thin strands with little evidence of denaturation. (31); and (b) titration of dilute solutions with 0.1 N NaOH (31). Repeated tests showed that the deviations in the concentrations of the prepared solutions from the value determined by weighing were always less than 5 per cent, which is about the limit of accuracy of the analytical tests employed.…”
Section: Dnamentioning
confidence: 97%